The Use of Tangram Teaching Aids in Learning Plane Geometry for 8th-Grade Students - Rini Utami; Dewi Azizah; Amalia Fitri; Muhamad Najibufahmi; Dewi Mardhiyana; Nurina Hidayah; Sayyidatul Karimah; Dwi Ario Fajar (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Our activity aims to assist 8th-grade students at SMP Plus Muhammadiyah Doro in learning Geometry using tangram teaching aids. This is related to the lack of enthusiasm some students feel during the learning process, especially in Geometry. The community service activity was carried out through planning, implementation, and evaluation stages, using lectures, discussions, experiments, and demonstrations. The instruments used include questionnaires given to students before and after the activity. The results of this activity show that: 1) almost all students contend that teachers now need tangrams to help in explaining teaching materials in Plane Geometry; 2) almost all students are interested in the tangrams, which is due to their ease of making and using; 3) almost all students contend that tangrams can help them to train their understanding of mathematical concepts, especially in plane figures; 4) most students believe that tangrams can enhance their motivation to learn.